(untitled) (Research, Society and Development, 2022)
This article discusses the Brazilian educational policy in its historical context, as its objectives it proposes to analyze the educational policies in the Brazilian scenario from the colony to the redemocratization in 1988 and to promote a current reflection about the equality of conditions, access, permanence and quality of formal schooling in Brazil. national scope in light of current legislation. The central question that guided this work consisted of the affirmative premise that the public policies implemented by the Brazilian State, historically consisted of mere government policies, varying in space and time according to the interests and directions imposed by capital and international organizations. As a main result, we can say that historically the educational policy implemented by Brazil was and still is associated with the interests of capital and international organizations, and consequently dissociated from the needs and interests of the less favored classes, not actually materializing the equality for all enshrined in the Constitution of 1988. In view of the researched object and the pursuit of the proposed objectives, bibliographic research was used, and the findings were analyzed in the light of dialectical historical materialism, making use of its classic categories, in particular, the movement, historicity and contradiction.